Analisis Kelayakan Finansial Pengolahan Kompos dari Limbah Ternak, Perkebunan dan Pengolahan Sawit oleh Kelompok Tani di Kabupaten Tanjung Jabung Barat - Firmansyah, Firmansyah; Hoesni, Fachroerrozi; H, Afriani; Trisilo, Tito Febriansyah (Ekonomis: Journal of Economics and Business, 2025)
This study aims to analyze the financial feasibility of compost processing by farmer groups in Purwodad and Dataran Kempas Villages, Tebing Tinggi District, West Tanjung Jabung Regency. The research method used is a survey method. The data obtained are primary and secondary data. Data analysis uses Net Present Value (NPV), Net Benefit Cost Ratio (Net B/C), Internal Rate of Return (IRR). The results of this study conclude that the farmer groups processing compost from cattle waste, plantation waste, and palm oil processing waste by farmer groups in Dataran Kempas Village are higher when compared to farmer groups in Purwodadi Village in Tebing Tinggi District, West Tanjung Jabung Regency.